Rancangan Aliran Proses dalam Upaya Meminimumkan Proses Non-Value Added melalui Value Stream Mapping pada UD Usaha Rezeki Prabot - Nurmalawati, Nurmalawati; Dewiyana, Dewiyana; Yusnawati, Yusnawati; Pramanda, Ryan; Rahman, Muhammad Abdul; Muzakir, Muzakir (Jurnal Optimalisasi, 2025)
The flow of process is a sequence of jobs or activities performed in producing goods and services. UD. Usaha Rezeki Prabot, a small-to-medium enterprise (SME) in furniture manufacturing, consistently faces a critical operational challenge: despite stable customer demand (853 units/year of panel door type 7), only 750 units (88%) are delivered on time, resulting in a 12% delay rate. This gap is not caused by insufficient labor or machinery, but by a fragmented production system riddled with non-value-added (NVA) activities particularly repetitive machine setup, excessive material handling, redundant measurements, and long waiting times that inflate lead time to 176.91 minutes per unit. Value Stream Mapping (VSM) is applied as a lean tool to visualize the entire material and information flow, identify dominant wastes (waiting, over-processing, and unnecessary motion), and redesign the workflow. Through the implementation of future-state mapping by grouping components with identical profiles into batch processing and eliminating redundant inspections the NVA time was reduced from 79.95 minutes (45.19%) to 16.07 minutes (15.93%), cutting total lead time by 43%. This study demonstrates that for SMEs like UD. Usaha Rezeki Prabot, sustainable productivity gains come not from capital investment, but from restructuring workflow based on frontline insights to eliminate systemic waste embedded in daily routines. The purpose of this mapping is to identify all types of waste along the Value Stream and to take a move in an attempt to eliminate the waste. The flow of process design with Value Stream Mapping approach enables the company to be able to minimize the non value added activities and to shorten the time taken in the process of making doors and to increase the productivity. The purpose of this Motion and Time study was to do a direct observation about time and movement of someone who is working. UD Rezki Prabot uses the VSM (Value Stream Mapping) to minimize the non value added process and to propose a design to improve the flow of process. The result of this study showed that the time of non value added activities decreased from 176.91 minutes to 100.9 minutes. The non value added activities decreased from 45.19% to 15.93% due to the decrease of non value added activities by sequencing the work activities that the machine does not need to be set up repeatedly.